Cadmium Accumulation Involves Synthesis of Glutathione and Phytochelatins, and Activation of CDPK, CaMK, CBLPK, and MAPK Signaling Pathways in Ulva compressa - González, Alberto; Laporte, Daniel; Moenne, Alejandra (Frontiers in Plant Science, 2021)
The alga Ulva compressa cultivated with 10, 25 and 50 µM of cadmium for 7 days and the level of intracellular cadmium was determined. Intracellular cadmium showed an increase at day 1, no change until day 5, and an increase at day 7. Then, the alga was cultivated with 10 µM for 7 days and the level of hydrogen peroxide, superoxide anions and lipoperoxides; activities of antioxidant enzymes ascorbate peroxidases (AP), dehydroascorbate reductase (DHAR) and glutathione reductase (GR); the level of glutathione (GSH) and ascorbate (ASC); the level of phytochelatins (PCs) and transcripts encoding metallothioneins (UcMTs) levels were determined. The level of hydrogen peroxide increased at 2 and 12 h, superoxide anions at day 1, and lipoperoxides at days 3 to 5. The activities of AP and GR were increased, but not DHAR activity. The level of GSH increased at day 1, decreased at day 3 and increased again at day 5 whereas ASC slightly increased at days 3 and 7, and activities of enzymes involved in GSH and ASC synthesis were increased. The level of PC2 and PC4 decreased at day 3 but increased again at day 5. The level of transcripts encoding UcMT1 and UcMT2 increased at day 3 to 5, mainly that of UcMT2. Thus, cadmium accumulation induced an oxidative stress condition that was mitigated by the activation of antioxidant enzymes and synthesis of GSH and ASC. Then, the alga cultivated with inhibitors of CDPKs, CaMKs, CBLPKs and MAPKs and 10 µM of cadmium for 5 days showing a decrease in intracellular cadmium and in the level of GSH and PCs, with the four inhibitors, and in the level of transcripts encoding UcMTs, with two inhibitors. Thus, CDPKs, CaMK, CBLPKS and MAPKs are involved in cadmium accumulation and GSH and PCs synthesis, and GSH and PCs and/or UcMTs may participate in cadmium accumulation.